PART I: APPLICATIONS OF SEMIPINACOL REARRANGEMENT REACTIONS ON THE SYNTHESIS OF MACROCYCLIC KETONES AND AXIALLY CHIRAL BIARYLS; PART II: SYNTHESIS AND CHARACTERIZATION OF BENZO [1,2-C,4,5-C']BIS[1,2,5]THIADIAZOLE BASED DIRADICALOIDS AND NEAR-INFRARED DYES - LIU YI (2017)
Ph.D